Kinetic Monte Carlo theory of sliding friction - Furlong, Octavio Javier (2009)
The sliding friction as a function of scanning velocity at the nanometer scale was simulated based on a modified one-dimensional Tomlinson model. Monte Carlo theory was exploited to describe the thermally activated hopping of the contact atoms, where both backward and forward jumps were allowed to occur. By comparing with the Monte Carlo results, improvements to current semiempirical solutions were made. Finally, experimental results of sliding friction on a NaCl(100) as a function of normal load and scanning velocity where successfully simulated. © 2009 The American Physical Society.